Nutrient uptake and rhizosphere microbial community as related to yield advantage in broomcorn millet‒alfalfa intercropping under different row configurations - Shengzhican Li; Ashanjiang Yiminijiang; Ruoxuan Li; Mandi Wu; Mingxiu Long; Peizhi Yang; Shubin He (BMC Plant Biology)
Abstract To investigate the effects of row ratio configurations on intercropping advantages and related rhizosphere microbial communities, a field experiment involving five treatments of different rows of broomcorn millet, i.e., P1M1 (1 row of broomcorn millet intercropped with 1 row of alfalfa), P2M3, P1M2, P1M3 and broomcorn millet alone (SP), was conducted on the Loess Plateau of China. We analyzed the yield, nutritional content of broomcorn millet, the soil nutrient availability and the diversity and community composition of AMF (arbuscular mycorrhizal fungi) and diazotrophs in the rhizosphere of broomcorn millet. The results showed that compared with monocultures, alfalfa-millet intercropping system under different row ratio configurations significantly increased the yield of broomcorn millet and the absorption of PTP and PTK (total phosphorus and potassium of broomcorn millet). In addition, the broomcorn millet-alfalfa intercropping system also improved soil nutrition, with the decrease of the row ratio of broomcorn millet, the changes of TN, NH4 +-N and microbial biomass in the rhizosphere of broomcorn millet were consistent, which was opposite to NO3 −-N. Moreover, co-occurrence network and PLS-PM (partial least squares path modelling) analysis showed alfalfa-broomcorn millet intercropping system changed the community diversity and composition of soil microorganisms, increased the improvement of soil nutrition (TN, NH4 +-N and microbial biomass), and promoted the absorption of different nutrients by plants (N, P and K) mainly through the negative regulation of AMF and the synergistic effect of AMF on diazotrophs, and finally increased crop yield. This shows that broomcorn millet-alfalfa intercropping can increase plant nutrient content by adjusting soil nutrients and soil microbial activities, thereby increasing yield. Furthermore, we found that 1P2M was the best ratio of alfalfa-millet intercropping system, which may provide reliable suggestions and selection basis for future agricultural production practices.